Peace, Freedom, and Social Justice.: Essay on the Rejection of Institutionalism. (Interdisciplinary Studies Journal, 2021)
The aim is to reflect on the concepts of peace and justice, seeking to establish a theoretical connection between Johan Galtung and Amartya Sen, questioning the institutionalist role that many authors and institutions still uphold regarding these two concepts, advocating the idea that institutional peace and justice alone are not enough for a truly peaceful, just, and egalitarian society.
Keywords: Peace; Institutionalism; Freedom; Justice